Effects of Iron and Temperature on Expression of the Pseudomonas aeruginosa tolQRA Genes: Role of the Ferric Uptake Regulator - Lafontaine, Eric R. (American Society for Microbiology, 1998)
The tolQRA genes have been recently identified in Pseudomonas aeruginosa PAO. In this study, we examined the effect of iron and temperature on tolQRA expression. A promoterless lacZ gene was introduced downstream of plasmid-encoded tolQ and tolA, and expression was monitored by measuring β-galactosidase activity of cultures. Addition of 25 μM FeCl(3) to the culture medium reduced tolQRA expression by 50 to 60% in PAO but by only 25% in the fur mutant PAO A4. Northern hybridization analysis revealed that iron regulation occurs at the level of transcription and involves the P. aeruginosa ferric uptake regulator (Fur). Primer extension analysis was used to identify the proposed transcriptional start site of tolA. Although a putative Fur box was identified 20 bp upstream of the proposed start site, purified Fur did not bind to the tolA or tolQR promoter regions in an in vitro gel retardation assay. Therefore, iron regulation of the tol genes appears to involve an intermediate regulatory gene. Expression of tolQR and tolA was optimal at 37°C and was reduced by 40 to 50% when cultures were grown at either 42 or 25°C. Growth in high-iron medium at 25°C further reduced tolQR and tolA expression.